The last of England? - Stevenson, Randall (Oxford : Oxford University Press, 2004)
Charting developments in the literary field since 1960, this book pinpoints the origins of literary change in the historical, social, and intellectual pressures of the times. It also covers the shadows of war and loss of empire; declining influences of class; shifting relations between the genders; emergent minority and counter-cultures; and more.
TOC Introduction: Last Things First; I. HISTORIES; 1. 'Gleaming Twilight': Literature, Culture, and Society; 2. A Postmodern Age? Literature, Ideas, and Traditions; 3. An Age of Theory? Critics, Readers, and Authors; 4. A Golden Age? Readers, Authors, and the Book Trade; II. POETRY; 5. Movement or Revival: The late 1950s to the 1980s; 6. Counter-movements and Modernist Memories: 1960 to the 1980s; 7. Politics and Postmodernism: The Late 1970s to 2000; 8. Rosebay Revived: Language, Form, and Audience for 'This Unpopular Art'; III. DRAMA; 9. A Public Art Form: The late 1950s to the 1970s; 10. Last Year in Jerusalem: Politics and Performance after 1968; 11. 'Real Revolutionaries': Politics and the Margins; 12. Absurdism, Postmodernism, Individualism; 13. Discovering the Body; 14. Revolution, Television, Subsidy; IV. NARRATIVE; 15. To the Crossroads: Style and Society in the 1960s and 1970s; 16. A Darker Route: Morality and History in the 1960s and 1970s; 17. Longer Shadows and Darkness Risible: The 1970s to 2000; 18. 'Double Lives': Women's Writing and Gender Difference; 19. 'The Century of Strangers': Travellers and Migrants; 20. Genres, Carnivals, and Conclusions; Author Bibliographies; Suggestions for Further Reading; Preface; I. HISTORIES; 1. 'Gleaming Twilight' - Literature, Culture, and Society; 2. A Postmodern Age? - Literature, Ideas, and Traditions; 3. An Age of Theory? - Critics, Readers, and Authors; 4. A Golden Age? - Readers, Authors, and the Book Trade; II. POETRY; 5. Movement or Revival - the late 1950s to the 1980s; 6. Movements and Counter-Movements - the 1960s to the 1980s; 7. Politics and Postmodernism - the late 1970s to 2000; 8. Rosebay Revived - Language, Form, and Audience for 'This Unpopular Art'; III. DRAMA; 9. A Public Art Form - the late 1950s to the 1970s; 10. Last Year in Jerulsalem - Politics and Performance after 1968; 11. 'Real Revolutionaries' - Politics and the Margins; 12. Absurdism, Postmodernism, Individualism; 13. Discovering the Body; 14. Revolution, Television, Subsidy; IV. NARRATIVE; 15. To the Crossroads - Style and Society in the 1960s and 1970s; 16. A Darker Route - Moral and Historical Vision in the 1960s and 1970s; 17. Longer Shadows and Darkness Risible - the 1970s to 2000; 18. 'Double Lives' - Women's Writing and Gender Difference; 19. 'The Century of Strangers' - Travellers and Migrants; 20. Genres, Carnivals, and Conclusions; Author Bibliographies; Suggestions for Further Reading; Works Cited; Index
Includes bibliographical references and index.
English
Sagar Shahanawaz
Keywords: English literature -- 20th century -- History and criticism